Criminal Liability For Perpetrators of Negligent Crimes Resulting in the Death of Others in Traffic Accidents - Hasbi, Fariz Rifqi; Utari, Anak Agung Dewi; Aringga, Rino Dedi (Sinergi International Journal of Law, 2023)
Criminal responsibility leads to the prosecution of the perpetrator who has committed a criminal act and fulfills its elements as stipulated in the law. Viewed from the perspective of the occurrence of a prohibited act (obligation), an individual will be criminally accountable for such actions if they are against the law. To hold someone criminally accountable, one must consider the culpability of the perpetrator. However, it is not sufficient to consider only the culpability; one must also consider the reasons and circumstances that eliminate the penalty as outlined in Articles 44, 48, 49, 50, and 51 of the Indonesian Penal Code (KUHP). In cases where the perpetrator has met the provisions of those articles, they are exempted from the threat of criminal charges. The research method used is normative juridical, which involves legal research on primary and secondary legal materials, especially those related to the discussed subject matter. This study aims to determine how criminal responsibility is imposed on perpetrators of negligent crimes resulting in the death of others in traffic accidents. From the research findings, it is concluded that the defendant Mariyanto, based on the trial facts, did not meet the criteria set forth in Articles 44, 48, 49, 50, and 51 of the KUHP that would eliminate the penalty. Therefore, Mariyanto can be held responsible and subject to criminal accountability. Considering that the victim also bears some responsibility contributing to the commission of the offense and that the defendant had no malicious intent, posing no danger, the writer suggests that the defendant should be appropriately sentenced to probation, as proposed by Mariyanto's Legal Counsel in their plea, taking into account humanitarian and justice considerations.